Role of the Center of Mass Correction in Magnetic Form Factors for 19O and 21Na Exotic Nuclei with Different Interactions - Hawi, M. H.; Dakhil, Z. A.; Hameed, B. S. (Iraqi Journal of Science, 2024)
The transverse magnetic electron scattering form factors of 19O and 21Na exotic nuclei were studied in the plane wave Born approximation (PWBA). The shell model calculations with three sd-shell interactions, USDA, USDB, and Wildenthal, were carried out for the ground and low-lying excited states. The exact center of mass correction in the Born approximation picture through the translation-invariant shell model (TISM) was included to modify the transverse form factors. The measured magnetic dipole moments were well reproduced with the core polarization (CP) effect introduced through the effective g-factors. The occupancies percentage with respect to the valence nucleons was also calculated.